Some Results on the Spectral Radius of Banach Algebra (Journal of Informatics and Mathematical Sciences, 2022)
Al-Banach algebra was introduced in 1940 by Russian mathematician I.M. Gelfand and arose from the observation that some Banach spaces exhibit interesting properties when they can be provided with operations and examples. Among the linear functions adopted in Al-Banach commutative algebra and its maxima, as well as with the spectra of its elements in one way or another that leads us towards the central component of the spectra mapping theory and the spectral radius formula. In this paper, we get some results on the spectral radius of Al-Banach algebra.